Amphiphilic graphene quantum dot dispersion liquid and preparation method thereof
By using pyrene as a construction unit, combined with nitration and hydrothermal synthesis methods, the number of edge hydroxyl groups and crystallinity of graphene quantum dots were regulated, and amphiphilic graphene quantum dots were prepared, which solved the problem of poor preparation and dispersion of graphene quantum dots, and achieved excellent amphiphilic performance and emulsion stability in a wide range of acid and alkali environments.
Patent Information
- Application Number
- CN202510090263.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-21
- Publication Date
- 2025-03-14
- Estimated Expiration
- 2045-01-21
AI Technical Summary
The preparation of graphene quantum dots is limited by the difficulty in preparation methods and dispersion, and it is difficult to prepare on a large scale, and the application of hydrophilic graphene quantum dots in oil phase media is limited.
The small molecule pyrene is used as the construction unit to prepare graphene quantum dots by first nitration and then hydrothermal synthesis, and the preparation of amphiphilic graphene quantum dots is achieved by controlling the alkali concentration and regulating the number and crystallinity of edge hydroxyl groups.
The pH usage range of graphene quantum dots has been successfully expanded, so that it can show excellent amphiphilic properties in acid-base environments, improve the density and stability of the emulsion, and expand its application potential in the fields of emulsion polymerization, interface reaction and nano-oil repellency.
Smart Images

Figure CN119612502A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of nano-carbon materials, and in particular relates to an amphiphilic graphene quantum dot dispersion liquid and a preparation method thereof. Background Art
[0002] In recent years, carbon quantum dot materials have attracted extensive attention in the fields of medical bioimaging, optical devices, and drug carrier materials due to their unique optical properties, low toxicity, and good biocompatibility. In the future, the application of carbon quantum dot materials will be even broader. Graphene quantum dots (GQDs), as an important branch of carbon dot materials, have been shown to have a more regular crystalline structure and higher fluorescence quantum yield than other carbon dot materials. However, the preparation of graphene quantum dots is limited by the preparation method and the difficulty of dispersion, making it difficult to prepare on a large scale.
[0003] In terms of preparation methods, the method of preparing graphene quantum dots using a "bottom-up" approach with small organic molecules as structural units has outstanding advantages such as clear preparation mechanism, easy regulation of groups, and easier modification. However, carbon dot products prepared by the "top-down" method of carbonization and cracking of carbon-based materials as raw materials have a natural disadvantage in terms of crystallinity. Therefore, it is very necessary to optimize the production steps and expand the production scale while ensuring the quality of graphene quantum dot products based on the "bottom-up" method.
[0004] The dispersibility of graphene quantum dots in different media will significantly affect their properties and applications. Materials can be divided into hydrophilic, hydrophobic and amphiphilic according to their dispersibility in water and non-polar organic solvents. The type and number of graphene quantum dot surface groups play a vital role in regulating their dispersibility. Most graphene quantum dots have good hydrophilicity due to the introduction of polar groups (e.g., hydroxyl, amino, hydrazine, etc.) during the preparation process. Hydrophilic graphene quantum dots are difficult to use in oil phase media, which limits its application in many fields. By regulating and modifying the surface groups, graphene quantum dots can be given some unique interfacial activity and emulsifying properties. Compared with traditional molecular emulsifiers, the emulsion prepared by amphiphilic graphene quantum dots is denser and has better emulsion stability. This means that compared with single hydrophilic or hydrophobic graphene quantum dots, amphiphilic graphene quantum dots have greater development potential in the fields of emulsion polymerization, interfacial reaction, nano-oil displacement, etc. Summary of the invention
[0005] In view of the current problems of hydrophilicity and hydrophobicity regulation of graphene quantum dots and preparation of amphiphilic graphene quantum dots, the present invention provides an amphiphilic graphene quantum dot dispersion liquid and a preparation method thereof which can facilitate scale-up production, has good dispersibility and can be used in a wide range of acidic and alkaline environments.
[0006] The present invention uses small molecule pyrene as a building block and adopts a "bottom-up" method of nitration followed by hydrothermal synthesis to prepare graphene quantum dots. By controlling the concentration of alkali (NaOH) during the preparation process, the number of hydroxyl groups at the edge of the graphene quantum dots and the crystallinity are regulated. In an alkaline environment, the phenolic hydroxyl groups at the edge of the graphene quantum dots will lose hydrogen protons to become polar hydrophilic groups, while the sp 2 The hybridized region is non-polar, and this difference between the inside and outside of the basal plane and the edge is the reason why graphene quantum dots have amphiphilic properties in a weakly alkaline environment.
[0007] The method for preparing an amphiphilic graphene quantum dot dispersion according to the present invention comprises the following steps:
[0008] (1) adding powdered pyrene to concentrated nitric acid having a mass fraction of 65 to 68 wt%, and reflux nitrifying at a certain temperature;
[0009] (2) After the reaction system of step (1) is cooled to room temperature, a large amount of pure water is added to dilute it, so that the product 1,3,6-trinitropyrene is flocculated; then, it is filtered with a 0.22 μm filter membrane, and the solid product is washed with pure water for multiple times to remove residual nitric acid until the pH of the reaction system is neutral, and the product is dried to obtain yellow 1,3,6-trinitropyrene;
[0010] (3) adding the 1,3,6-trinitropyrene obtained in step (2) to a sodium hydroxide solution of a certain concentration, transferring it to a polytetrafluoroethylene reactor after ultrasonic dispersion, and performing a hydrothermal reaction at a certain temperature to prepare graphene quantum dots;
[0011] (4) adjusting the pH of the graphene quantum dots obtained in step (3) to an acidic state with dilute sulfuric acid or acetic acid to flocculate the graphene quantum dots; washing the bottom precipitate with pure water after centrifugation and centrifuging several times to obtain a paste of graphene quantum dots, quenching the paste with liquid nitrogen, and freeze-drying the paste to obtain powdered amphiphilic graphene quantum dots;
[0012] (5) ultrasonically dispersing the amphiphilic graphene quantum dots obtained in step (4) in a Tris-HCl buffer solution at a certain concentration to obtain a brown-black amphiphilic graphene quantum dot dispersion;
[0013] (6) dispersing disodium hydrogen phosphate dodecahydrate and sodium dihydrogen phosphate dihydrate in a water system at a certain concentration, and ultrasonically dispersing the amphiphilic graphene quantum dots obtained in step (4) in the water system at a certain concentration to obtain a brown-black amphiphilic graphene quantum dot dispersion;
[0014] Preferably, in step (1), the concentration of pyrene in the concentrated nitric acid system is 12.5 to 20 g / L, the nitration temperature is 70 to 90° C., and the nitration time is 10 to 12 h;
[0015] Preferably, the concentration of the sodium hydroxide solution in step (3) is 2 to 16 mg / mL, wherein the concentration of 1,3,6-trinitropyrene in the sodium hydroxide solution is 3 to 6 mg / mL; the temperature of the hydrothermal reaction is 150 to 210° C., and the reaction time is 6 to 8 hours;
[0016] Preferably, in step (4), the concentration of dilute sulfuric acid is 1 to 2 mol / L, and the concentration of acetic acid is 10 to 17.5 mol / L;
[0017] Preferably, the concentration of the Tris-HCl buffer solution in step (5) is 0.04-0.1 mol / L, and the pH is 7.1-7.5; the concentration of the amphiphilic graphene quantum dots in the obtained amphiphilic graphene quantum dot dispersion is 1-5 mg / mL;
[0018] Preferably, the mass concentration of disodium hydrogen phosphate dodecahydrate in the water system of step (6) is 22 to 30 g / L, the mass concentration of sodium dihydrogen phosphate dihydrate is 2.5 to 6 g / L, and the concentration of amphiphilic graphene quantum dots in the obtained amphiphilic graphene quantum dot dispersion is 1 to 5 mg / mL.
[0019] The obtained dispersion was mixed with toluene, cyclohexane or n-octane in equal volumes, ultrasonically emulsified and allowed to stand for 12 hours, the emulsification rate was measured and the microscopic state of the emulsified bubbles was observed under a microscope;
[0020] The obtained dispersion was diluted and adjusted to different gradient pH values with sodium hydroxide or hydrochloric acid, and further mixed with an equal volume of n-octane, ultrasonically emulsified and allowed to stand for 12 h, the emulsification rate was determined, and the microscopic state of the emulsified bubbles was observed under a microscope.
[0021] Some embodiments of the present invention provide a method for preparing amphiphilic graphene quantum dots, which adopts a strategy of acidification with dilute sulfuric acid and acetic acid, greatly simplifying the existing graphene quantum dot preparation steps. The prepared powdered graphene quantum dot product has pH responsiveness due to the presence of surface phenolic hydroxyl groups, and exhibits very excellent dispersion performance in alkaline systems, but is difficult to disperse in acidic-neutral aqueous solutions. The present invention successfully expands the pH use range of amphiphilic graphene quantum dots by using Tris-HCl in a neutral range and a Na2HPO4 / NaH2PO4 water dispersion system. It can exhibit excellent amphiphilic properties to various oil phases such as toluene, cyclohexane, and n-octane in the acid-base range of pH=1 to 13. The emulsion prepared with the amphiphilic graphene quantum dots is dense, the emulsified bubble particle size is small, and it has very excellent stability. BRIEF DESCRIPTION OF THE DRAWINGS
[0022] Figure 1The infrared absorption spectrum (IR) images of 1,3,6-trinitropyrene prepared in Example 1 and raw material pyrene;
[0023] Figure 2 This is the infrared absorption spectrum image of GQDs-48 prepared in Example 2;
[0024] Figure 3 a is a transmission electron microscope (TEM) image of GQDs-48 prepared in Example 2; Figure 3 b is a local magnified image of quantum dots in a transmission electron microscope image; Figure 3 c is the Bragg diffraction spot pattern obtained after the lattice fringes are subjected to Fourier transform (FFT); Figure 3 d is the measurement diagram of lattice fringe spacing;
[0025] Figure 4 The X-ray diffraction pattern (XRD) of the GQDs series products prepared in Example 2 between 10 and 40°;
[0026] Figure 5 Dynamic light scattering diagram of the particle size distribution of GQDs-48;
[0027] Figure 6 The emulsification rate and average emulsion droplet size distribution diagram of the mixed emulsion system of Tris-HCl (pH=7.4) dispersion of GQDs series products and cyclohexane, toluene, and n-octane;
[0028] Figure 7 This is an optical microscope microscopic morphology of emulsion droplets of a mixed emulsion system of Tris-HCl (pH=7.4) dispersion of GQDs series products and cyclohexane, toluene, and n-octane;
[0029] Figure 8 The emulsification rate and average emulsion droplet size distribution diagram of GQDs-48 and A-GQDs-48 products in the mixed emulsion system of Na2HPO4 / NaH2PO4 water dispersion system and cyclohexane, toluene, and n-octane;
[0030] Fig. 9 The emulsification rate and average emulsion droplet size distribution diagram of the mixed emulsion system of the aqueous dispersion in the bag after GQDs-48 dialysis and n-octane at pH = 1, 3, 5, 7, 9, 11, and 13.
[0031] Fig.10 a is the emulsification rate and average emulsion droplet size distribution of GQDs-48 product in the mixed emulsion system of Na2HPO4 / NaH2PO4 water dispersion system and cyclohexane, toluene and n-octane; Fig.10b is the emulsification rate and average emulsion droplet size distribution of A-GQDs-48 product in the mixed emulsion system of Na2HPO4 / NaH2PO4 water dispersion system and cyclohexane, toluene and n-octane;
[0032] Fig.11 a is the emulsification rate and average emulsion droplet size distribution of A-GQDs-48 product in Tr-HCl (pH=7.4) water dispersion system and mixed emulsion system of cyclohexane, toluene and n-octane; Fig.11 b is the emulsification rate and average emulsion droplet size distribution of A-GQDs-48 product in the mixed emulsion system of Na2HPO4 / NaH2PO4 water dispersion system and cyclohexane, toluene and n-octane; DETAILED DESCRIPTION
[0033] In order to describe the technical elements, effect advantages and use environment of the prepared product of the present invention in more detail, a specific description will be made in conjunction with specific embodiments below. Based on the embodiments of the present invention, ordinary technicians in this field directly obtain this embodiment without creative activities, which belongs to the scope of protection of the present invention. The raw materials and instruments used in the present invention can be purchased through normal commercial channels. The present invention is further described below in conjunction with the accompanying drawings and embodiments:
[0034] Example 1
[0035] Add 1g of ground pyrene to 50mL of concentrated nitric acid (mass fraction 65%), stir and mix, and then nitrate at 80℃ for 12h. After the reaction system is allowed to stand and cool, add 1L of pure water to dilute the system to promote the precipitation and flocculation of 1,3,6-trinitropyrene from the concentrated nitric acid reaction system. Use suction filtration to pass the reaction product through a 0.22μm nylon filter membrane, and wash the solid product with pure water several times to remove residual nitric acid until the pH of the reaction system is neutral. The collected product is placed in a vacuum oven at 60℃ and dried to obtain yellow 1,3,6-trinitropyrene with a yield of 96.0%. Figure 1 The infrared spectra of pyrene and nitropyrene are compared. The nitration product 1,3,6-trinitropyrene has obvious nitro characteristic peaks, including 1518cm -1 The antisymmetric stretching vibration peak of the nitro group is at 1350cm -1 The symmetrical stretching vibration peak of the nitro group is at 892 cm -1 The peak is the stretching vibration peak of the CN bond.
[0036] Example 2
[0037] Weigh 150 mg of 1,3,6-trinitropyrene prepared in Example 1, add it to 30 mL of 16 mg / mL sodium hydroxide solution, and use a probe ultrasonic disperser to ultrasonically disperse it at 450 W for 5 minutes. The uniformly dispersed system was transferred to a 50 mL polytetrafluoroethylene reactor and hydrothermally reacted at 180 ° C for 8 hours. After the reaction, 10 mL of 1 mol / L dilute sulfuric acid solution was added to the system to adjust the pH to acidic (pH = 3.5) to promote graphene quantum flocculation. The graphene product was collected by centrifugation and washed three times with pure water to remove residual Na + 、SO4 2- Plasma was used to obtain a paste of graphene quantum dots, which was quenched with liquid nitrogen and freeze-dried to obtain a powdered graphene quantum dot product named GQDs-48 with a product mass of 80 mg. Figure 2 The infrared absorption peak of GQDs-48, the stretching vibration peak of C-OH is at 1259cm -1 The stretching vibration peak of OH is at 3350 cm -1 The absorption intensity of the two characteristic absorption peaks is large, which indicates that the surface of the graphene quantum dot product prepared by the present invention has abundant hydroxyl functional groups. The infrared stretching vibration peak of the graphene quantum dot structure C=C is at 1580cm -1 Place. Figure 3 A transmission electron microscope image of GQDs-48 is given, and it is measured that the average particle size of the quantum dots prepared by the present invention is 2.94 nm. Figure 3 The Bragg diffraction spots in c are obvious, indicating that it has very excellent crystallinity. Figure 3 d shows the lattice fringes of graphene quantum dots, with a spacing of 0.211 nm, belonging to the (100) crystal plane of graphene.
[0038] The concentration of the sodium hydroxide solution was lowered to 2 mg / mL, and the other steps were exactly the same as the preparation method of GQDs-48. The prepared product was named GQDs-6.
[0039] The concentration of the sodium hydroxide solution was lowered to 4 mg / mL, and the other steps were exactly the same as the preparation method of GQDs-48. The prepared product was named GQDs-12.
[0040] The concentration of the sodium hydroxide solution was lowered to 8 mg / mL, and the other steps were exactly the same as the preparation method of GQDs-48. The prepared product was named GQDs-24.
[0041] The concentration of the sodium hydroxide solution was lowered to 12 mg / mL, and the other steps were exactly the same as the preparation method of GQDs-48. The prepared product was named GQDs-36.
[0042] The pH was adjusted to acidic (pH = 3.5) with 1 mol / L dilute sulfuric acid instead of 12 mol / L acetic acid (pH = 3.5). The remaining steps were exactly the same as the preparation method of GQDs-48. The prepared product was named A-GQDs-48.
[0043] The yield of the graphene quantum dot series products prepared above is between 82% and 94%. Table 1 shows the C=C infrared absorption vibration peak (1580cm -1 ) and the antisymmetric stretching vibration peak of the nitro group (1518 cm -1 ) absorption intensity ratio, it can be clearly seen that with the increase of sodium hydroxide concentration, the content of residual nitro groups continues to decrease, and the reaction of the raw material 1,3,6-trinitropyrene is more complete. The post-treatment process of acidification with dilute sulfuric acid and acetic acid has no significant difference in the infrared and structural properties of the final product. The XRD spectrum of the GQDs series products is Figure 4 It is shown that 26.4° is the characteristic peak of the (002) crystal plane of graphene quantum dots. The small particle size of the quantum dots causes the characteristic peak to exist in the form of a broad peak. Figure 5 This is the statistical particle size distribution diagram of the alkaline aqueous dispersion (pH=13) of the GQDs-48 product measured by dynamic light scattering technology (DLS). The hydrated particle size of the GQDs-48 product is 3.25 nm, which is slightly larger than the average particle size measured by TEM electron microscopy.
[0044] Table 1: 1580 and 1518 cm in the infrared spectra of GQDs series products -1 The absorption intensity ratio data of the peak
[0045]
[0046] Example 3
[0047] The graphene quantum dot series products prepared in Example 2 showed dispersion differences in aqueous solutions with different pH values due to the presence of edge phenolic hydroxyl groups. 1 mol / L solution systems were prepared with sodium hydroxide and concentrated hydrochloric acid, respectively, and the corresponding pH values were 13 and 1. 1 mol / L hydrochloric acid was gradually diluted with water to prepare hydrochloric acid solutions with pH = 3 and 5, and 1 mol / L sodium hydroxide was gradually diluted with water to prepare sodium hydroxide solutions with pH = 8, 9, and 11. At a concentration of 0.2 mg / mL, the series of GQDs products prepared in Example 2 were added to the water system with gradient pH values obtained by diluting with sodium hydroxide and hydrochloric acid, respectively, to explore the dispersion effect.
[0048] As shown in Table 2, the GQDs series products prepared in Example 2 have excellent dispersibility in an alkaline environment of pH>9. After dispersion in an alkaline aqueous solution, the system presents a uniform brown-red color, while the dispersion effect is poor in acidic and neutral water systems. Most of the GQDs products exist at the bottom of the solution in the form of precipitation, and the system only appears as a light yellow-green color. Among them, although the A-GQDs-48 product prepared by acetic acid acidification also shows difficulty in dispersion at pH=1, 3, 5, and 7 like other products, its degree of dispersion is better than other graphene quantum dot products prepared by dilute sulfuric acid acidification.
[0049] Table 2: Dispersibility of GQDs series products prepared in Example 2 in aqueous solutions with different pH values (× represents difficult dispersion; √ represents good dispersion)
[0050]
[0051] Tris-HCl buffer solution is widely used in biochemistry and molecular biology experiments, and graphene quantum dots are a potential candidate for biological fluorescent probes with high fluorescence yield, good stability and low biological toxicity. Therefore, it is very necessary to consider the dispersion performance of graphene quantum dots in Tris-HCl buffer solution. The present invention uses tris (Tris) and hydrochloric acid as raw materials to prepare a Tris-HCl buffer solution with a pH value of 7.1 to 7.5 and 0.05 mol / L. The GQDs series products prepared in Example 2 are added to a 0.05 mol / L Tris-HCl buffer solution at a concentration of 2 mg / mL, and ultrasonicated for 5 minutes. The GQDs series products can be completely dispersed in a system with a pH value of 7.1 to 7.5, and appear as a dark brown-red color, indicating that the graphene quantum dot products of the present invention have very excellent dispersion performance in Tris-HCl buffer solution.
[0052] Inorganic salt co-solvents are extremely effective in improving the dissolution and dispersion properties of poorly soluble substances. The present invention dissolves 2.9g of Na2HPO4·12H2O and 0.3g of NaH2PO4·2H2O in 100mL of water. The GQDs series products prepared in Example 2 are added to the Na2HPO4 / NaH2PO4 solution at a concentration of 2mg / mL, and ultrasonicated for 5min. The GQDs series products can be completely dispersed in the system and appear dark brown-red, indicating that the graphene quantum dot products of the present invention have very excellent dispersion properties in the Na2HPO4 / NaH2PO4 solution.
[0053] Example 4
[0054] The GQDs series products prepared in Example 2 were dispersed in a Tris-HCl buffer solution with a pH of 7.4, and the concentration was 2 mg / mL. 3 mL of the dispersion was mixed with an equal volume of an organic oil phase (n-octane, cyclohexane, toluene, etc.), and ultrasonically dispersed for 2 min at a power of 270 W. The mixture was allowed to stand for 12 h. After the emulsion was stable, the emulsification rate of the sample was measured (emulsification rate = V 乳化层体积 / V 总体积 *100%). The state of the emulsified bubbles was observed and studied using a microscope, and the particle size of the emulsified bubbles was measured and analyzed. Figure 6 This is an analysis chart of the emulsification rate and emulsified bubble particle size of the GQDs series products. The Tris-HCl buffer solution of the GQDs series products shows excellent emulsification effect in a variety of organic oil phases such as n-octane, cyclohexane, toluene, etc. The prepared emulsion system is dense, and can still reach an emulsification rate of more than 75% after standing for 12 hours, and the average particle size of the emulsified bubbles is only 10-20 μm. The amphiphilic properties of the GQDs series products prepared by the present invention are positively correlated with the sodium hydroxide concentration. During the preparation process, as the sodium hydroxide concentration increases, the Tris-HCl dispersion (pH=7.4) of the GQDs series products is mixed with a variety of organic oil phases such as cyclohexane, toluene, and n-octane for ultrasonic emulsification, and its emulsification effect is continuously improved (emulsification rate increases, emulsified bubble particle size decreases, the line represents the emulsification rate, and the bar graph represents the emulsified bubble particle size). That is, the concentration of sodium hydroxide used in the subsequent preparation of amphiphilic graphene quantum dots should be 16 mg / mL. The A-GQDs-48 product obtained by acetic acid treatment has better emulsification performance (higher emulsification rate and smaller emulsion droplets) than the GQDs-48 product. We attribute this performance improvement to the fact that acetic acid, as a weak acid, reduces the hard agglomeration of graphene quantum dots during the acidification flocculation process, making it easier to disperse the subsequent amphiphilic graphene quantum dot product.
[0055] Figure 7 The emulsion bubble microscope state diagram of the GQDs series products dispersed in Tris-HCl (pH=7.4) dispersion and an equal volume of organic oil phase (n-octane, cyclohexane, toluene, etc.) emulsion is displayed. The results show that the particle size of the prepared emulsion is uniform and the emulsion system is dense.
[0056] Example 5
[0057] Na2HPO4·12H2O and NaH2PO4·2H2O were added to the pure water system at concentrations of 29 g / L and 3 g / L, respectively. The GQDs-48 and A-GQDs-48 products prepared in Example 2 were dispersed in the Na2HPO4 / NaH2PO4 system at 2 mg / mL, and ultrasonically dispersed to obtain a brown-black dispersion. 3 mL of the dispersion was mixed with an equal volume of an organic oil phase (n-octane, cyclohexane, toluene, etc.), ultrasonically dispersed for 2 minutes at a power of 270 W, and allowed to stand for 12 hours. After the emulsion was stable, the emulsification rate of the sample was determined. The state of the emulsified bubbles was observed under a microscope, and the particle size of the emulsified bubbles was determined and analyzed. Figure 8 This is the emulsification rate and emulsified bubble particle size analysis chart of GQDs-48 and A-GQDs-48 products. In the Na2HPO4 / NaH2PO4 dispersion system, both GQDs-48 and A-GQDs-48 products showed excellent amphiphilic emulsification performance. The emulsification rates of both in three organic oil phases were 65-80%, and the particle size of the emulsion droplets was 15-20μm. The emulsification performance of A-GQDs-48 product was slightly better than that of GQDs-48 product.
[0058] Example 6
[0059] The GQDs-48 prepared in Example 2 was directly transferred to a 3500Da dialysis bag before acidification, and dialyzed continuously for 2 days. The concentration of the graphene quantum dot aqueous dispersion in the dialysis bag was measured to be 2.2 mg / mL, and the dispersion was directly diluted to 2 mg / mL with water. Afterwards, dilute hydrochloric acid (3 mol / L) and sodium hydroxide solution (3 mol / mL) were used to adjust the pH values to 1, 3, 5, 7, 9, 11, and 13, respectively. 3 mL of the GQDs-48 graphene quantum dot gradient pH dispersion was mixed with an equal volume of n-octane, ultrasonically dispersed at a power of 270 W for 2 minutes, and allowed to stand for 12 hours. After the emulsion was stabilized, the emulsification rate was measured at different pH values, and the state of the emulsified bubbles was studied by microscopic observation. According to Fig. 9 It can be seen from the emulsification bubble line graph and the emulsification bubble average particle size bar graph that GQDs-48 can have a higher emulsification rate only under strong acid or strong alkaline conditions (pH = 1 or 13), indicating that the use of pure GQDs aqueous dispersion is affected by the pH of the water system and its use environment has great limitations.
[0060] Example 7
[0061] Na2HPO4·12H2O and NaH2PO4·2H2O were added to the pure water system at concentrations of 29 g / L and 3 g / L, respectively, to obtain a Na2HPO4 / NaH2PO4 aqueous solution system, and the GQDs-48 prepared in Example 2 was prepared into a dispersion at a concentration of 2 mg / mL. The dispersion was adjusted to pH 1, 3, 5, 7, 9, 11, and 13 with dilute hydrochloric acid (3 mol / L) and sodium hydroxide solution (3 mol / mL), respectively, and diluted to 1 mg / mL with pure water. 3 mL of the GQDs-48 graphene quantum dot gradient pH dispersion was mixed with an equal volume of n-octane, ultrasonically dispersed at 270 W for 2 min, and allowed to stand for 12 h. After the emulsion was stable, the emulsification rate at different pH values was determined, and the average particle size distribution of the emulsified bubbles was studied by microscopic observation.
[0062] The GQDs-48 in the above content was replaced by A-GQDs-48, the concentration of the graphene quantum dot dispersion was replaced by 1 mg / mL, and the other conditions remained unchanged.
[0063] according to Fig.10 The emulsification bubble line graph and the emulsification bubble average particle size bar graph show that the emulsification rate of the emulsion prepared by GQDs-48 and A-GQDs-48 products can still be maintained at 65-75% after standing for 12 hours. The emulsion droplet size of GQDs-48 at a concentration of 2 mg / mL is 5-35 μm, and the emulsion droplet size of A-GQDs-48 at a concentration of 1 mg / mL is 15-75 μm.
[0064] Example 8
[0065] The GQDs-48 prepared in Example 2 was dispersed in a Tris-HCl (pH = 7.4) system at a concentration of 4 mg / mL to prepare a dispersion. The dispersion was adjusted to pH 1, 3, 5, 7, 9, 11, 13 with dilute hydrochloric acid (3 mol / L) and sodium hydroxide solution (3 mol / mL), and diluted to 2 mg / mL with pure water. 3 mL of the GQDs-48 graphene quantum dot gradient pH dispersion was mixed with an equal volume of n-octane, ultrasonically dispersed at 270 W for 2 minutes, and allowed to stand for 12 hours. After the emulsion was stable, the emulsification rate at different pH values was determined, and the average particle size distribution of the emulsified bubbles was studied by microscopic observation.
[0066] The GQDs-48 in the above content was replaced by A-GQDs-48, the concentration of the graphene quantum dot dispersion was replaced by 1 mg / mL, and the other conditions remained unchanged.
[0067] according to Fig.11The emulsification bubble line graph and the emulsification bubble average particle size bar graph show that the emulsification rate of the emulsion prepared by GQDs-48 and A-GQDs-48 products can still be maintained at 55-75% after standing for 12 hours. The emulsion droplet size of GQDs-48 at a concentration of 2 mg / mL is 5-45 μm, and the emulsion droplet size of A-GQDs-48 at a concentration of 1 mg / mL is 5-85 μm.
[0068] Combining Example 7 and Example 8, it is found that the lower limit of the concentration of A-GQDs-48 for emulsification is lower than that of GQDs-48 dispersion. A-GQDs-48 dispersion concentration of 1 mg / mL can form an emulsion with an equal volume of n-octane, while GQDs-48 requires 2 mg / mL. Comparing Example 6 with Examples 7 and 8, it is found that the graphene quantum dot Tris-HCl dispersion and Na2HPO4 / NaH2PO4 dispersion prepared by the present invention greatly expand the scope of use of amphiphilic graphene quantum dots. The two system dispersions prepared by us can achieve two-phase emulsification (aqueous phase / organic oil phase) of pH=1-13 system. The prepared emulsion has the characteristics of high emulsification rate, good stability, dense emulsion and small emulsion droplets, and has good commercial value in the fields of emulsifiers, oil displacement agents, and biochemical scientific research.
Claims
1. A method for preparing amphiphilic graphene quantum dots, the steps of which are as follows: (1) adding powdered pyrene to concentrated nitric acid having a mass fraction of 65 to 68 wt%, and reflux nitrifying at a certain temperature; (2) After the reaction system of step (1) is cooled to room temperature, a large amount of pure water is added to dilute it, so that the product 1,3,6-trinitropyrene is flocculated; then, it is filtered with a 0.22 μm filter membrane, and the solid product is washed with pure water for multiple times to remove residual nitric acid until the pH of the reaction system is neutral, and the product is dried to obtain yellow 1,3,6-trinitropyrene; (3) adding the 1,3,6-trinitropyrene obtained in step (2) to a sodium hydroxide solution of a certain concentration, transferring it to a polytetrafluoroethylene reactor after ultrasonic dispersion, and performing a hydrothermal reaction at a certain temperature to prepare graphene quantum dots; (4) adjusting the pH of the graphene quantum dots obtained in step (3) to an acidic state with dilute sulfuric acid or acetic acid to flocculate the graphene quantum dots; washing the bottom precipitate with pure water after centrifugation and centrifuging several times to obtain a paste of graphene quantum dots, quenching the paste with liquid nitrogen, and freeze-drying the paste to obtain powdered amphiphilic graphene quantum dots; (5) ultrasonically dispersing the amphiphilic graphene quantum dots obtained in step (4) in a Tris-HCl buffer solution at a certain concentration to obtain a brown-black amphiphilic graphene quantum dot dispersion; (6) dispersing disodium hydrogen phosphate dodecahydrate and sodium dihydrogen phosphate dihydrate in a water system at a certain concentration, and ultrasonically dispersing the amphiphilic graphene quantum dots obtained in step (4) in the water system at a certain concentration to obtain a brown-black amphiphilic graphene quantum dot dispersion.
2. A method for preparing amphiphilic graphene quantum dots as claimed in claim 1, characterized in that: In step (1), the concentration of pyrene in the concentrated nitric acid system is 12.5-20 g / L, the nitration temperature is 70-90° C., and the nitration time is 10-12 h.
3. A method for preparing amphiphilic graphene quantum dots as claimed in claim 1, characterized in that: In step (3), the concentration of the sodium hydroxide solution is 2 to 16 mg / mL, wherein the concentration of 1,3,6-trinitropyrene in the sodium hydroxide solution is 3 to 6 mg / mL; the temperature of the hydrothermal reaction is 150 to 210° C., and the reaction time is 6 to 8 hours.
4. A method for preparing amphiphilic graphene quantum dots as claimed in claim 1, characterized in that: In step (4), the concentration of dilute sulfuric acid is 1-2 mol / L, and the concentration of acetic acid is 10-17.5 mol / L.
5. A method for preparing amphiphilic graphene quantum dots as claimed in claim 1, characterized in that: The concentration of the Tris-HCl buffer solution in step (5) is 0.04-0.1 mol / L, and the pH is 7.1-7.5; the concentration of the amphiphilic graphene quantum dots in the obtained amphiphilic graphene quantum dot dispersion is 1-5 mg / mL.
6. A method for preparing amphiphilic graphene quantum dots as claimed in claim 1, characterized in that: The mass concentration of disodium hydrogen phosphate dodecahydrate in the water system of step (6) is 22-30 g / L, the mass concentration of sodium dihydrogen phosphate dihydrate is 2.5-6 g / L, and the concentration of amphiphilic graphene quantum dots in the obtained amphiphilic graphene quantum dot dispersion is 1-5 mg / mL.
7. An amphiphilic graphene quantum dot dispersion, characterized in that: The method is prepared by any one of claims 1 to 6.
Citation Information
Patent Citations
fluorescence determination of LIPOLYTIC ENZYME ACTIVITY
ATA102994A
Boron-doped graphene quantum dot, and preparation method and application thereof
CN107586540A
Amphiphilic graphene quantum dot as well as preparation method and application thereof
CN108300463A
Application of electrochemical biosensor based on gold-graphene quantum dots in detection of ctDNA in cells
CN112986361A
Amphiphilic graphene quantum dot modified by water-soluble pillararene, preparation method and application thereof
CN113278416A